Especialización económica del Municipio de Zapopan y Jalisco estrategias basadas en los recursos y capacidades - Bautista Ramírez, Martha Lizbeth (2018)
The objective of this research focuses on the analysis of economic specialization of the municipality of Zapopan Jalisco, for the years 1999 and 2009. Also study based on the resources and capacities of economic branches strategy to find sources potential benefits, competitive advantage between the municipality and the state, and development processes. The study method is based on a theoretical analysis and report and literature review. The results focus on the location coefficient (Cl *) to check the basic jobs in economic activities. Along with the application of the theory mentioned above. The subject is given a qualitative approach; since the data will be obtained from the economic census (INEGI) during the period 1999 and 2014.